Saint Kitts and Nevis. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Saint Kitts and Nevis during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as public policies, innovation, nutrition, sustainability, food safety, handling, risk management, labeling, livestock, plant and animal health. Likewise, work was done on drought management, improving safety processes, drought management, combating pest risks, through a list of regulated pests and quality processes. Finally, it supported the use of greenhouses to feed children, food processing and mango cultivation.